COEXISTENCE AND INTEGRATION: AN ANALYSIS OF SOCIAL DYNAMICS BETWEEN MUHAMMADIYAH AND NU IN RURAL AREAS - Muh Zakki Amrulloh; Ishomuddin; M. Rondi; Jefri Mardiansyah A. (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The topic of coexistence and integration between Muhammadiyah and Nahdlatul Ulama (NU) in rural areas is highly relevant in the Indonesian social context. These two largest Islamic organizations play an important role as pillars of social harmony, especially in areas vulnerable to social change due to modernization and globalization. This study aims to analyze the social dynamics between Muhammadiyah and NU in rural areas, focusing on coexistence and integration as efforts to strengthen community solidarity. The method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, participant observation, and analysis of relevant documents. Data triangulation is used to validate the findings. The results show that coexistence between Muhammadiyah and NU is achieved through collaboration in social activities such as education and health, despite the challenges posed by ideological differences. The contribution of this study is to provide a practical model for building harmony among groups in rural areas, applicable to social policy. This study concludes that this coexistence has positive implications for Indonesia's social stability and suggests that further research using quantitative surveys is needed to measure the long-term impact of this integration.